The legacy of church-state conflict: Evidence from Nazi repression of Catholic priests - Leonid Peisakhin; Didac Queralt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
A burgeoning literature on repression against civilians argues that exposure to violence changes victims' identities by strengthening attachment to the in-group and creates downstream effects for political and social behaviour that persist across generations. In this paper, we ask whether selective repression against community elites, who are crucial in the processes of value formation and transmission, might create similar lasting effects. We test this hypothesis in the context of Nazi-era repression of Catholic clergy in Bavaria and explore whether historical repression against Catholic priests might be associated with higher support for Christian Democrats in the post-World War II period. Consistent with expectations, we find that communes where Catholic priests had been repressed by the Nazi regime are more likely to vote for Christian Democrats by comparison to those settlements where no elite repression took place. This effect is particularly strong in smaller communes where networks are tighter and where the repressed priests served for longer periods. We find that the legacy of priest repression on voting behaviour persists all the way into the present, although its magnitude wanes overtime. These findings shed new light on the long-term political repercussions of the church-state relationshipand suggest that selective repression of elites is capable of leaving lasting intergenerational legacies for political and social behaviour.
Keywords: N44; P48; 330; church-state relationship; elite repression; Nazi regime; Catholic clergy; Christian Democrats; Bavaria